2012
DOI: 10.1038/leu.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Selective, novel spleen tyrosine kinase (Syk) inhibitors suppress chronic lymphocytic leukemia B-cell activation and migration

Abstract: Syk is a protein tyrosine kinase that couples B-cell receptor (BCR) activation with downstream signaling pathways, affecting cell survival and proliferation. Moreover, Syk is involved in BCR-independent functions, such as B cell migration and adhesion. In CLL, Syk becomes activated by external signals from the tissue microenvironment, and was targeted in a first clinical trial with R788 (fostamatinib), a relatively non-specific Syk inhibitor. Here, we characterize the activity of two novel, highly selective Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 41 publications
(70 reference statements)
6
98
0
Order By: Relevance
“…S1B). This SYK inhibitor has been validated in previous studies, where it showed suppression of BCR-dependent SYK activity in B cells (18,19). Upon induction of shRNAs targeting CD79a in DG75 cells, we observed a profound reduction of CD79a expression leading to diminished expression of BCR on the cell surface ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…S1B). This SYK inhibitor has been validated in previous studies, where it showed suppression of BCR-dependent SYK activity in B cells (18,19). Upon induction of shRNAs targeting CD79a in DG75 cells, we observed a profound reduction of CD79a expression leading to diminished expression of BCR on the cell surface ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…Recent evidence demonstrated that it is also expressed by many non-hematopoietic cell types (Hoeler et a1., 2005;Ulanova et a1., 2005) and that it plays a negative role in cancer (Hoellenriegel et al, 2012). A significant drop in its expression was first observed during breast cancer progression, but an anomalous Syk expression has now also been evidenced in many other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…79 Using a combinatory approach of DLBCL biopsies and cell lines, it has been shown that chronically active BCR signaling in ABC-DLBCL can be dependent on BTK-dependent signaling or can be elicited by somatic mutations affecting the immunoreceptor tyrosine-based activation motif (ITAM) signaling modules of CD79B and CD79A and also can be influenced by mutations in the signaling adaptor CARD11 which can lead to enhanced NF-kB signaling in ABC-DLBCL. 77 These results highlight the therapeutic potential of targeting BCR downstream effectors with specific pharmacological agents like dasatinib, for the SRC family of tyrosine kinase inhibitors, 80 SYK inhibitors, 8 ibrutinib (PCI-32765), a selective BTK inhibitor of proven value in the treatment of relapsed/refractory B-cell malignancies, 47,81 or CAL-101, a PI3Kd inhibitor. 82 Our perspective on the mutational landscape governing DLBCL pathogenesis has improved after learning that a number of nuclear proteins that control chromatin structure and gene expression harbor mutations like MLL2, a histone methyltransferase that is inactivated in 24-32% of cases, 32,68 MEF2B (15.7% reported by Morin et al…”
Section: Diffuse Large B-cell Lymphomamentioning
confidence: 98%
“…2 In addition to this, we now know that signaling from the B-cell receptor 3,4 and co-receptors (CD19, Toll-like receptors) 5,6 can be considered as triggers for activating critical signaling pathways that regulate a range of biological activities in B-cell lymphomas, including altered metabolism, 7 enhanced proliferation and survival, 1 and cell migration in response to soluble factors. 8 These highlight the increasing interest in developing BCR downstream signaling inhibitors with the potential for use in clinical practice. Despite the great efforts made towards understanding the critical mechanisms governing B-cell lymphomagenesis, and the amount of data already generated, we are still faced with an imperfect scenario in which many well-defined clinicopathological entities still lack specific genetic markers with a pathogenic role, and where the clinical diversity of many of these conditions remains partially unexplained.…”
Section: Introductionmentioning
confidence: 99%